Vehicle Communication System Using Li-Fi Technology (International Journal of Engineering and Computer Science, 2017)
In this paper, presents the designs of a small-scale prototype of a vehicle to vehicle communication system using light fidelity (Li-Fi) technology. The new technology that was developed in the last few years, which still needs more investigations on its sustainability for outdoor vehicular networks. The vehicle to vehicle communication is the most effective solution that has been used in order to reduce vehicles’ accidents. The proposed use of Li-Fi technology comprises mainly light-emitting diode (LED) bulbs as means of connectivity by sending data through light spectrum as an optical wireless medium for signal propagation. In fact, the usage of LED eliminates the need of complex wireless networks and protocols. In this work, several case studies are, presents to mimicking the vehicle to vehicle communication. The numerical simulations are done by using proteous package and the experimental results are also presented. The proposed system gives better results in both simulation and hardware